Psychodrama in therapeutic communities for drug addiction: A study of four cases investigated using idiographic change process analysis. (November 2018) - Testoni, Ines; Cecchini, Clara; Zulian, Maria; Guglielmin, Maria Silvia; Ronconi, Lucia; Kirk, Kate; Berto, Flaviana; Guardigli, Chiara; Cruz, Ana Sofia
Abstract: Many psychotherapeutic models, including psychodrama, have tried to address the problem of drug-addiction and alcoholism within, and outside, therapeutic communities (TCs). The dearth of literature related to the application of psychodrama in TCs means that significant efforts are needed to show its effectiveness. This article derives from a TC in northern Italy and presents a study of four cases, which analyzed the results of a 6 month psychodrama research intervention that adopted the Person Centered Approach (PCA). The effects were measured through an idiographic change process with a mixed method design. The qualitative part of the assessment consisted of the Client Change Interview (CCI), the Helpful Aspects of Therapy (HAT); the longitudinal quantitative part used the Spontaneity Assessment Inventory − Revised (SAI-R), the Clinical Outcomes in Routine Evaluation − Outcome Measure (CORE-OM), the General Self-Efficacy Scale (GS-ES), and the Pro.Spera. The changes in main personality factors were evaluated through Minnesota Multiphasic Personality Inventory (MMPI). Results suggested on the one hand that psychodrama therapy may increase patients' self-awareness and motivation to change their way of life and improve the PCA. On the other hand the qualitative methodology of HAT and CCI demonstrated, and monitored, the process of change and empowerment in the patients. Finally, the subject of gender specificity is explored.